2009
DOI: 10.1090/s0894-0347-09-00636-5
|View full text |Cite
|
Sign up to set email alerts
|

SLE and the free field: Partition functions and couplings

Abstract: Schramm-Loewner Evolutions (SLE) are random curves in planar simply connected domains; the massless (Euclidean) free field in such a domain is a random distribution. Both have conformal invariance properties in law. In the present article, some relations between the two objects are studied. We establish identities of partition functions between different versions of SLE and the free field with appropriate boundary conditions; this involves ζ \zeta -regularization and the Polyakov-Alvarez confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
276
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 170 publications
(283 citation statements)
references
References 44 publications
(136 reference statements)
6
276
0
Order By: Relevance
“…3.3. (As stated in [6], the theorem was conditional on the existence of solutions to a certain SDE, but we will prove this existence in Sect. 2.)…”
Section: η (T) = E I(h(η(t))/χ +θ)mentioning
confidence: 98%
See 4 more Smart Citations
“…3.3. (As stated in [6], the theorem was conditional on the existence of solutions to a certain SDE, but we will prove this existence in Sect. 2.)…”
Section: η (T) = E I(h(η(t))/χ +θ)mentioning
confidence: 98%
“…2,3,4,5). Several works in recent years have addressed special cases and variants of this question [6,8,10,19,28,31,37] and have shown that in certain circumstances there is a sense in which the paths are well-defined (and uniquely determined) by h, and are variants of the Schramm-Loewner evolution (SLE). In this article, we will focus on the case that z is point on the boundary of the domain where h is defined and establish a more general set of results.…”
Section: η (T) = E I(h(η(t))/χ +θ)mentioning
confidence: 99%
See 3 more Smart Citations